To solve the equation \( x^2 + 2x = 3 \) using the function graph method, we can first rewrite the equation in standard form:
\[ x^2 + 2x - 3 = 0 \]
Now, we can define a function \( f(x) \) based on the left side of the equation:
\[ f(x) = x^2 + 2x - 3 \]
To find the solutions to the equation, we need to determine where the graph of \( f(x) \) intersects the x-axis, which occurs when \( f(x) = 0 \).
Steps:
- Finding the Roots: We can use the quadratic formula to find the roots of the equation:
\[ x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \]
In our case:
- \( a = 1 \)
- \( b = 2 \)
- \( c = -3 \)
Calculating the discriminant:
\[ b^2 - 4ac = 2^2 - 4(1)(-3) = 4 + 12 = 16 \]
Now, substituting the values into the quadratic formula:
\[ x = \frac{{-2 \pm \sqrt{16}}}{2 \cdot 1} = \frac{{-2 \pm 4}}{2} \]
Calculating the potential solutions:
- \( x = \frac{{-2 + 4}}{2} = \frac{2}{2} = 1 \)
- \( x = \frac{{-2 - 4}}{2} = \frac{{-6}}{2} = -3 \)
Solutions:
The solutions to the equation \( x^2 + 2x = 3 \) are:
\[ x = -3 \quad \text{and} \quad x = 1 \]
Conclusion:
The options provided included:
- \( x = -3, 1 \)
- no solution
- \( x = 2, 0 \)
- \( x = 0, 1 \)
The correct response is:
x = -3, 1